Comparison of reported outdoor activities in Florida State Parks among three fitness tracker apps. (1st January 2023) - Schirck-Matthews, Angela; Hochmair, Hartwig; Paulus, Gernot
Abstract: This research used activity data from three fitness tracker apps (AllTrails, MapMyFitness, Wikiloc) to assess which features of Florida State Parks and their surroundings are associated with the number of hiking, cycling, running, and paddling activities. Key features, such as the density of hiking or cycling trails in and population near parks were associated with increased activity levels across most activity types. Comparison of regression results among apps gave insight into the consistency of app use for each specific outdoor activity type. The study also examined which apps are favored to track specific activities. Comparison to other studies sheds some light on user biases likely caused by analyzing a tech-savvy subgroup of outdoor enthusiasts who have access to mobile tracker apps. Therefore, sport-activity counts obtained from GPS tracker apps should be used with caution or be cross-referenced with other data sources, such as on-site questionnaires, for calibration.